INPOWER-CARE Sebagai Implementasi Community Relations pada PT. Indonesia Power Suralaya PGU (Studi Kasus Program Mitra Binaan Omah Kreteg Anggana) - M.Farhan Fahrudin; Siska Mardiana; Annisarizki Annisarizki (Universitas Serang Raya, 2021)
INPOWER-CARE programs as the implementation of Community Relations is the fostered partner of Omah Kreteg Anggana, this activity aims to develop skills and welfare for the community, especially around the company by promoting the Suralaya locality, namely sambal kreteg. The purpose of this study was to determine the implementation and development of the INPOWER-CARE program of Omah Kreteg Anggana's fostered partners as the implementation of the Community Relations program. This study used a qualitative approach with case study methods and data collection techniques by conducting observations, in-depth interviews with four informants, documentation and literature. The results of this study indicate that the Division of Public Relations and Community Development PT. Indonesia Power Suralaya PGU in implementing the program, Community Relations, namely by maintaining relationships with the community by conducting socialization needed by the community and establishing intimacy with the people who participate in the program. Meanwhile, in developing the program of Omah Kreteg Anggana's fostered partners, they carried out institutional strengthening in accordance with the RENSTRA and RENJA. With the implementation of this program, the relationship between the company and the community is getting closer and mutually beneficial to one another.